A Case Report of Spontaneous Pneumomediastinum Following Chest Massage: A Rare Clinical Presentation - Naveed Ul Hassan H; Kowsthubha B G; Amaravathi Uthayakumar (Clinical Practice and Cases in Emergency Medicine, 2026)
Introduction: Spontaneous pneumomediastinum is a rare condition characterized by the presence of air in the mediastinum without preceding trauma. It is often triggered by minor events such as coughing, physical exertion, or traditional therapies. Case Report: A 52-year-old male with a history of pulmonary tuberculosis developed sudden left-sided chest pain and swelling following traditional chest massage therapy. Examination revealed subcutaneous emphysema with palpable crepitus. Imaging showed characteristic signs of pneumomediastinum with bilateral lung opacities. As a complication of pneumomediastinum the patient developed mediastinitis and a mediastinal abscess, requiring open thoracotomy and drainage. He recovered with multidisciplinary care. Conclusion: Early recognition of spontaneous pneumomediastinum in emergency settings is crucial, especially when chest pain is accompanied by subcutaneous emphysema, to prevent serious complications.